2017
DOI: 10.1002/2017gl074706
|View full text |Cite
|
Sign up to set email alerts
|

Multidecadal Weakening of Indian Summer Monsoon Circulation Induces an Increasing Northern Indian Ocean Sea Level

Abstract: North Indian Ocean sea level has shown significant increase during last three to four decades. Analyses of long‐term climate data sets and ocean model sensitivity experiments identify a mechanism for multidecadal sea level variability relative to global mean. Our results indicate that North Indian Ocean sea level rise is accompanied by a weakening summer monsoon circulation. Given that Indian Ocean meridional heat transport is primarily regulated by the annual cycle of monsoon winds, weakening of summer monsoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 56 publications
1
35
0
Order By: Relevance
“…The results here support this and further document nutrient declines. There is also evidence of sea level rise and associated weakening of the summer monsoon in the Equatorial Indian Ocean in recent decades (Swapna et al 2017). Such weakening could reduce the upwelling of nutrients and suppress ocean PP as we find here.…”
Section: Resultssupporting
confidence: 67%
“…The results here support this and further document nutrient declines. There is also evidence of sea level rise and associated weakening of the summer monsoon in the Equatorial Indian Ocean in recent decades (Swapna et al 2017). Such weakening could reduce the upwelling of nutrients and suppress ocean PP as we find here.…”
Section: Resultssupporting
confidence: 67%
“…While some IOD events co-occur with ENSO, others are ENSO-independent (e.g., Meyers et al 2007; Sun et al 2015; Yang et al 2015). Additionally, variations of monsoon winds, which are often correlated with ENSO and IOD but sometimes act independently, also induce variability in sea level over the Indian Ocean (Han et al 2017b; Swapna et al 2017). In the south Indian Ocean, the subtropical Indian Ocean dipole (SIOD) was identified as a coupled ocean–atmosphere mode (Behera and Yamagata 2001; Suzuki et al 2004).…”
Section: The Indian Oceanmentioning
confidence: 99%
“…preindustrial-control simulation are shaded and zonal and meridional surface wind fields are shown as vectors in the figure. The AllForc experiment (Figure 14c) shows a weakening of monsoon circulation with reversal in monsoon cross-equatorial flow over the Arabian Sea, Bay of Bengal as well as over the Indian land mass similar to the observed trend in summer monsoon circulation (Krishnan et al, 2016;Swapna et al, 2017;Bollasina et al, 2011). The precipitation response from the AllForc Exp shows decrease in precipitation over the Indian region associated with the weakening of summer monsoon circulation.…”
Section: Climate Change Modeling Capabilitiesmentioning
confidence: 53%